Methodological approaches to the collection of information on the assessment of the intensity of recreational fishing - Buzevych, I.; Бузевич, І. Ю.; Maksymenko, M.; Максименко, М. Л.; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; et al. (Інститут рибного господарства Національної академії аграрних наук України, 2022)
Based on the analysis of ichthyological material obtained from the catches of recreational fishermen in the Kakhovka, Dnipro (Zaporizhzhia), Kamianske, Pechenezhsky reservoirs and their tributaries in different seasons of 2003–2022, the processing of the authors’ materials, methodological recommendations have been prepared for the collection of factual data on quantitative and qualitative parameters of recreational fishing in water bodies of Ukraine. The main parameters have been established, which are subject to control during the collection of actual data with their differentiation in accordance with the conditions of recreational fishing. Unified forms for recording collected data have been proposed. The prospect of further research is the development of an algorithm for calculating the quantitative parameters of the pressure on aquatic biological resources by recreational fishermen with the aim of introducing a single methodology for accounting for the quantitative and qualitative characteristics of recreational fishing in water bodies of Ukraine during scientific and environmental protection activities on inland water bodies of national importance. На основі аналізу іхтіологічного матеріалу, отриманого з уловів рибалок-любителів на Каховському, Дніпровському (Запорізькому), Кам’янському, Печенізькому водосховищах та їхніх притоках у різні сезони 2003–2022 рр., опрацювання авторських матеріалів підготовлені методичні рекомендації щодо збору фактичних даних стосовно кількісних та якісних параметрів любительського рибальства на водоймах України. Встановлені основні показники, які підлягають контролю при зборі фактичних даних з диференціацією їх відповідно до умов здійснення любительського рибальства. Запропоновані уніфіковані форми щодо фіксації зібраних даних. Перспективою подальших досліджень є розробка алгоритму розрахунку кількісних параметрів навантаження на водні біоресурси з боку рибалок-любителів з метою запровадження єдиної методики для обліку кількісних та якісних характеристик любительського рибальства у водоймах України при здійсненні наукової та природоохоронної діяльності на внутрішніх водних об’єктах загальнодержавного значення.
Методичні підходи до збору інформації щодо оцінки інтенсивності любительського рибальства
Новіцький Роман Олександрович https://orcid.org/0000-0001-9373-5759
Keywords: struktura ulovu; структура улову; vnutrishni vodoimy; внутрішні водойми; liubytelske rybalstvo; любительське рибальство; rekreatsiine rybalstvo; рекреаційне рибальство; zasoby lovu; засоби лову